Food and Its Culture in Ancient Arabic Proverbs - Abdeldeen, Mahmoud Talab Hasan (Dirasat: Human and Social Sciences, 2024)
Objectives: This research aims to highlight the significance of food and its various types, as well as its cultural representation in ancient Arabic proverbs in expressing the heritage and etiquette of the nation. Proverbs were chosen as they are popular literary art forms that have extensively documented Arab culture, including its customs and traditions, and they serve an educational purpose in guiding and influencing people's behavior. Methods: Employing a descriptive analytical approach, the research will focus on a sample of 174 proverbs that deal with food, and will extract the culture, customs, and wisdom of the Arab society through those proverbs found in the book "Majma' al-Amthal" by Abu al-Fadl al-Maydani. This source serves as a wellspring for extracting the embedded cultural contexts and societal mores related to food. Results: The analysis reveals that Arab cuisine's simplicity mirrors the region's resource availability, with a culinary palette that has both absorbed foreign influences and crafted unique social customs. Proverbs categorized meals in tune with daily activities, terms evolving semantically. They uphold values of generosity and hospitality, admonish miserliness, discourage unpermitted consumption, promote dietary moderation, and highlight the health merits of eating at specific times. Conclusions: Arabic food-related proverbs provide a dual function: documenting the gastronomic vocabulary of yore and reflecting the Arab world's moral judgments, customs, and dining protocols. These proverbs are vital to anthropological study, encapsulating and perpetuating cultural norms, thereby playing a key role in safeguarding Arab heritage